More is more: toddlers do not show choice overload - Castelo, Romulus J.; Kim, Seokyung; Carlson, Stephanie M. (Frontiers in Developmental Psychology, 2023)
Psychological theory and research demonstrate the positive effects of personal choice on human motivation. However, there is evidence in adults that an overabundance of options can lead to choice overload, when choices become demotivating. Little is known about the early development of behaviors involving choice. Across two studies, we investigated whether toddlers (M age = 2.5 years) preferred choice over non-choice and tested for the presence of choice overload using a novel sticker-book task. Moreover, we explored associations between children's executive function (EF) skills and choice preference behavior. In Study 1 (N = 106), children preferred choice on 70% of trials, and this preference increased as a function of the number of options from 2-26. There was no evidence of choice overload. Study 2 (N = 52) replicated findings from Study 1 with up to 53 options, but there was no linear effect. Age (inversely) and sex (female) predicted choice preference in Study 2. Some aspects of parent-reported EF were inversely related to children's preference for choice, whereas a direct assessment of EF was positively correlated, independent of age. Future research should test for choice overload using alternative measures with a wider age range and clarify associations between EF and choice preference.